Strategy of the Head of Administration in Improving the Performance of Education Personnel (Strategi Kepala Tata Usaha dalam Meningkatkan Kinerja Tenaga Kependidikan) - Evi Ajriani; Badarwan Badarwan; Samrin Samrin (Shautut Tarbiyah, 2022)
This study aims to examine the Strategy of the Head of Administration in Improving the Performance of Education Personnel at SMP N 10 Konawe Selatan. This study uses qualitative research. Data collection techniques were carried out by interviews, observation and documentation. Data analysis through the process of data reduction, data presentation and drawing conclusions as well as data validity techniques through data triangulation (technique, source and time), extending observations, and conducting Member checks. The results showed that: 1) The performance of teaching staff at SMP N 10 Konawe Selatan quite good in terms of Skp, increased archiving, and can complete work according to their responsibilities. 2) The strategy of the head of administration is to first carry out disciplinary coaching by making absences to be initialed during arrival and return hours, then providing motivation, giving awards, understanding a comfortable working atmosphere, including training and evaluations which are held at the end of each year.Keywords:     Head of Administration Strategy, Performance of Education Personnel